A Study of The Value of Life Struggle in The Main Character in The Novel “Dompet Ayah, Sepatu Ibu” by J.S. Khairen - Pratiwi, Triska; Eko Sri Israhayu (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
Economic downturns are considered to be one of the bad influences that impact human life. The main impact of the economic downturn is increasing poverty, unemployment and ignorance. The struggle against adversity is seen as something terrible. The reason is, the struggle you go through will always be haunted by failure. One depiction of struggle can be seen in literary works in the form of novels. The aim of this research is to explore the values ​​of life's struggle in the main character in the novel Dompet Ayah Shoes Ibu by J.S Khairen. The type of research used is qualitative with the research object focused on the values ​​of life's struggle in the novel Dompet Ayah Shoes Ibu by J.S Khairen. This research uses a literary sociology approach. This approach is closely related to the value of life's struggle. The data in this research was collected through reading and note-taking procedures which were presented in the form of quotations, dialogues, monologues and sentences that highlight various aspects of life's struggle values. Source triangulation was used in this research to ensure the validity of the data. The author analyzes research data through several stages, namely data collection, data reduction, data presentation, and verification or drawing conclusions. The results of this research show that there are values ​​of life struggle in the novel Dompet Ayah Shoes Ibu by J.S Khairen, which include the value of being willing to sacrifice, the value of unity, the value of respect, the value of patience, and the value of the spirit of never giving up.